1992
DOI: 10.1021/bi00140a013
|View full text |Cite
|
Sign up to set email alerts
|

Linkage of the acetylcholine transporter-vesamicol receptor to proteoglycan synaptic vesicles

Abstract: The relationship of the acetylcholine transporter-vesamicol receptor (AcChT-VR) to proteoglycan in Torpedo electric organ synaptic vesicles was investigated. The cholate-solubilized VR was immunoprecipitated by a monoclonal antibody directed against the SV1 epitope located in the glycosaminoglycan portion of the proteoglycan. AcChT that was photoaffinity-labeled with a tritiated high-affinity analogue of AcCh [cyclohexylmethyl cis-N-(4-azidophenacyl)-N-methylisonipecotate] and then denatured in sodium dodecyl … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1994
1994
2009
2009

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 44 publications
(37 reference statements)
0
9
0
Order By: Relevance
“…Our demonstration of homology between claustrin to the ENP 1 protein found in Torpedo electromotor neurons is interesting in light of recent evidence identifying a KSPG associated with the synaptic vesicles of Torpedo electric organ (Bahr et al, 1992). The partial Torpedo cDNA clone for ENP 1 is 70% homologous to the 5' region of the mouse MAP 1 B sequence, and appears to also represent a 5' truncated fragment of MAP 1 B (Ngsee and Scheller, 1989).…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…Our demonstration of homology between claustrin to the ENP 1 protein found in Torpedo electromotor neurons is interesting in light of recent evidence identifying a KSPG associated with the synaptic vesicles of Torpedo electric organ (Bahr et al, 1992). The partial Torpedo cDNA clone for ENP 1 is 70% homologous to the 5' region of the mouse MAP 1 B sequence, and appears to also represent a 5' truncated fragment of MAP 1 B (Ngsee and Scheller, 1989).…”
Section: Discussionmentioning
confidence: 59%
“…Several proteoglycans associated with synaptic vesicles and membranes in Torpedo have been characterized (Kiene and Stadler, 1987;Carlson and Wight, 1987). Recently, it has been reported that the acetylcholine transporter-vesamicol receptor complex ( AcChT-VR) of Torpedo synaptic vesicles is associated with a KSPG (Bahr et al, 1992). Although the exact identity of this KSPG has not been determined, it may be related to the cholinergic synaptic vesicle proteogiycan ( SVPG) previously described (Stadler and Dowe, 1982;Carlson and Kelly, 1983 ).…”
Section: Discussionmentioning
confidence: 94%
“…It is therefore of interest that a neuron-specific KS-substituted protein has been demonstrated in the Torpedo electric organ and in rat brain (13). This protein ("synaptoglycan" (4)) is located intracellularly in synaptic vesicles and has been implicated with the transport of acetylcholine (14). Conceivably, binding of the positively charged neurotransmitter to highly sulfated regions of KS may be critical to normal transport, which thus would be perturbed in AD.…”
Section: Discussionmentioning
confidence: 99%
“…Most pertinent are specific proteoglycans that have been shown to be involved in the mechanisms of neurotransmission (Bahr et al, 1992a) as well as in the formation and maintenance of neuromuscular junctions (Nastuk and Fallon, 1993). This broad spectrum of action may complicate the interpretations concerning the effects of heparin on AMPA receptors in intact preparations.…”
Section: Discussionmentioning
confidence: 99%
“…With the overall finding that heparin binds to and alters the properties of AMPA receptors, it is of interest that glycosaminoglycan-containing proteoglycans are abundant in the brain (Herndon and Lander, 1990) and are known to have effects on a large number of physiological processes (see Ruoslahti, 1989). Most pertinent are specific proteoglycans that have been shown to be involved in the mechanisms of neurotransmission (Bahr et al, 1992a) as well as in the formation and maintenance of neuromuscular junctions (Nastuk and Fallon, 1993). This broad spectrum of action may complicate the interpretations concerning the effects of heparin on AMPA receptors in intact preparations.…”
Section: Table II Change In [mentioning
confidence: 99%